2019
DOI: 10.1111/liv.14084
|View full text |Cite
|
Sign up to set email alerts
|

MACK‐3 (combination of hoMa, Ast and CK18): A promising novel biomarker for fibrotic non‐alcoholic steatohepatitis

Abstract: Abbreviations: 95% CI, 95% confidence interval; ALT, alanine aminotransferase; AST, aspartate aminotransferase; AUROC, area under the receiver operating characteristic curve; BMI, body mass index; CK18, cytokeratin 18; F, fibrosis stage; FIB-4, fibrosis-4 index; HbA1c, glycated haemoglobin; HOMA, homeostatic model assessment of insulin resistance; MACK-3, combination of hoMa, Ast and CK18; NAFLD, non-alcoholic fatty liver disease; NAS, NAFLD activity score; NASH, non-alcoholic steatohepatitis; NFS, NAFLD fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…To the Editor We read with interest the article by Chuah 1 This study validates a previous study by Boursier et al (2018) that provided an algorithm for the calculation of MACK-3, 2 followed by an online calculator (http://forge.info.univ-angers.fr/~gh/wstat/ mack3-calcu lator.php).…”
Section: Chai and Mack-3 As Noninvasive Indices For Nonalcoholic Steasupporting
confidence: 69%
“…To the Editor We read with interest the article by Chuah 1 This study validates a previous study by Boursier et al (2018) that provided an algorithm for the calculation of MACK-3, 2 followed by an online calculator (http://forge.info.univ-angers.fr/~gh/wstat/ mack3-calcu lator.php).…”
Section: Chai and Mack-3 As Noninvasive Indices For Nonalcoholic Steasupporting
confidence: 69%
“…Composed of three ingredients (HOMA, AST and CK-18) the AUC from the validation group (n = 846) was 0.85. MACK-3 had an AUC of 0.80 when evaluated in a separate study [24].…”
Section: Multimarker Models Including Ck-18mentioning
confidence: 94%
“…Three studies provided sufficient data for analysis of M30 in detecting fibrotic NASH, with a combined total of 1,271 participants (343 with fibrotic NASH) ( S5 Fig in S1 File). Two studies investigated M30 as part of a multimarker models; authors of both studies [24,55] provided accuracy data for M30 at seven threshold values we selected based on the data from the present meta-analysis (133, 200, 248, 292, 356, 395, and 464 U/L). This allowed us to apply the multiple thresholds model (15 thresholds), to calculate an AUC of 0.73 (95% CI: 0.57-0.85), mean sensitivity of 0.63 (95% CI: 0.39-0.82) and mean specificity of 0.73 (95% CI: 0.51-0.88) at a Youden-threshold value of 371 U/L.…”
Section: Plos Onementioning
confidence: 99%
“…We greatly appreciate the letter from Polyzos and Kountouras 1 and their comments in relation to our article. 2 It is interesting to note that Polyzos et al have reported the use of a similar combination of homeostatic model assessment of insulin resistance (HOMA-IR), aspartate aminotransferase (AST) and cytokeratin-18 (CK-18), called CHAI, for the diagnosis of nonalcoholic steatohepatitis (NASH). 3 While it is widely known that HOMA-IR, AST and CK-18 are indicators of insulin resistance, hepatocyte injury and apoptosis, respectively, and reasonable to expect these markers to be elevated in more severe nonalcoholic fatty liver disease (NAFLD), the development of an acceptable algorithm for diagnostic use is not as straightforward.…”
Section: Dear Editormentioning
confidence: 99%
“…The strength of MACK-3 lies in its ability to rule out fibrotic NASH given its excellent sensitivity and negative predictive value that were consistently shown in both studies. 2,5 With this test, the need for liver biopsy can hopefully be significantly reduced when screening for fibrotic NASH among the very large population of NAFLD patients.…”
mentioning
confidence: 99%